Gray Correlation Coefficient Analysis on the Mechanical Properties of Nylon Fiber Reinforced Recycled Aggregate Concrete with GGBS - Islam, Sk. Rakibul; Mutsuddy, Rupak; Shahid, Nishatee Binte (Civil Engineering Journal, 2025)
Rapid urbanization and infrastructure development intensify the demand for aggregate in concrete production. One efficient technique to reduce demolition and construction waste and produce sustainable concrete is using recycled aggregates. However, previous studies on recycled aggregate concrete (RAC) demonstrated that the mechanical characteristics are remarkably affected due to the adhered previous layers of mortar with the aggregate. Incorporating fibers and supplementary cementitious materials (SCMs) in the concrete mix is a common practice that enhances the mechanical characteristics of concrete and ensures sustainability by reducing carbon footprint. Previous studies lack the combination of nylon fiber (NF) and ground granulated blast furnace slag (GGBS), a by-product of the iron industry and treated as solid waste. Moreover, the research regarding the combined effect of the SCMs and fiber needs to cover the sensitivity of these constituents individually, according to statistical analysis. Hence, the main purpose of this research is to deal with the influence of incorporating NF and GGBS on the mechanical properties of concrete where recycled concrete aggregate was used. Moreover, the sensitivity of the properties with the percentage of replacement of binder and volume fraction (Vf) of nylon fiber was assessed using the Gray correlation coefficient. Compressive strength was dropped by around 10% when recycled material was substituted for natural aggregate. In contrast, adding 0.1% nylon fiber and 10% cement replacement with GGBS increased the crushing strength by about 10.9% compared to the conventional mix. In Gray's analysis, flexural toughness ranked higher in correlation with the controlling factors. Considering the environmental sustainability and the synergetic effect of nylon fiber and GGBS on mechanical properties, recycled aggregate is employable in concrete compared with the conventional concrete of natural stone aggregate. Doi: 10.28991/CEJ-2025-011-03-07 Full Text: PDF